SOSTENIBILIDAD DE UN PROGRAMA DE MICROFINANZAS RURALES Y SU APLICACIÓN EN LA PARROQUIA CHANDUY DEL CANTON SANTA ELENA. - TAMARA CARDENAS ASTUDILLO (2011)
SUSTAINABILITY OF A RURAL MICROFINANCE PROGRAM AND ITS APPLICATION IN THE CHANDUY PARISH OF SANTA ELENA CANTON.